Molecular Dynamics to Elucidate the DNA-Binding Activity of AlpZ, a Member of the Gamma-Butyrolactone Receptor Family in Streptomyces ambofaciens - Vicente, Cláudia M.; Girardet, Jean-Michel; Hôtel, Laurence; Aigle, Bertrand (Frontiers in Microbiology, 2020)
Signaling molecule receptors play a central role in quorum sensing and in the coordination onset of specialized metabolite biosynthesis in Streptomyces due to their dual function in signal detection and gene expression control through DNA-binding in the promoter region of their target genes. In Streptomcyes ambofaciens the alp biosynthetic gene cluster includes the signaling molecule receptor AlpZ that negatively regulates through a complex regulatory cascade the expression of key genes involved in the kinamycin antibiotic production until its cognate ligand, a yet unidentified signaling molecule, prompts its release from target promoters. Here we use an original molecular dynamics method to evaluate the DNA-binding properties of AlpZ to its target DNA sequence and the impact the signaling molecule has on the interaction. It is the first time this approach is used to characterize a regulator from the γ-butyrolactone receptor family. The observed KD in the nanomolar range indicates that AlpZ-DNA constitute a particularly stable complex. The signaling molecule ably disturbs this binding while kinamycin has no effect on the activity of AlpZ. Regulator size was determined and found to be considerably large regarding protein sequence, indicating that AlpZ regulates gene expression by binding the DNA as a homodimer, and structural modelling comparison with closely related γ-butyrolactone receptors supports this conclusion.